Q: How do you solve 2x - 3?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

2x + 3 is an expression that is already in simplest form; you cannot "solve" it.

2x - 3= 9 x=

2x+3 = 7 2x = 7-3 2x = 4 x = 2

If we assume that it equals zero and you wish to solve for x, then the answer is:-x2 + 2x - 3 = 0x2 - 2x + 3 = 0x2 -2x + 1 = -2(x - 1)2 = -2x - 1 = ± √(-2)x = 1 ± i√2

2x + 3 = 9 To solve Subtract '3' from both sides 2x = 6 Divide both sides by '2' x = 3 The Answer!!!!!

Related questions

2x + 3 is an expression that is already in simplest form; you cannot "solve" it.

2x + 3= 9.X=

2x - 3= 9 x=

2x+3 = 7 2x = 7-3 2x = 4 x = 2

2x-3=9 so 2x=12 and x=6

2x+3=9 x

2x 5 -7 = 3

2x+3 = -11 2x = -11-3 2x = -14 x = -7

2x + 3 = x 2x + 3 - 3 = x - 3 2x = x - 3 2x - x = x - 3 - x x = -3

4x2 - 9 = (2x + 3)(2x - 3)

If we assume that it equals zero and you wish to solve for x, then the answer is:-x2 + 2x - 3 = 0x2 - 2x + 3 = 0x2 -2x + 1 = -2(x - 1)2 = -2x - 1 = ± √(-2)x = 1 ± i√2

2x + 3 = 9 To solve Subtract '3' from both sides 2x = 6 Divide both sides by '2' x = 3 The Answer!!!!!